The state and cinema sector in neoliberal Turkey :|regulation or arbitrary intervention? - Özşen, Yeliz. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2019., 2019)
This study’s main purpose is to analyze the role of the state in the cinema industry of Turkey with a focus on the laws, regulations, and statistical data. These analyses dwell on the ways in which the cinema sector in Turkey has been influenced by the state policies particularly throughout the 1980s and afterwards that was characterized by neoliberalism and globalization. The analyses are also accompanied by a comparison of the relationship between the state and cinema sector in Turkey with France, the United States, and India. The historical and ethnographic data demonstrates that the Turkish state lacks policies to facilitate the cinema industry growth as a profitoriented sector; to protect national cinema against the domination of the foreign profitoriented cinema sectors; and/or to support the art cinema. The Turkish state gets involved in the sector only through some arbitrary and non coherent interventions and through the implementation of neoliberal policies, the sector is essentially abandoned to the market conditions. This abandonment eventually causes monopolization in various parts of the cinema sector. By highlighting these significantly under researched political economic dynamics, this thesis fills a gap in the literature on cinema in Turkey which so far has focused primarily on its historical and artistic dimensions.
Keywords: Motion pictures -- Turkey.